Female entrepreneurs and poverty reduction: hair craft SMEs in Tanzania. Issue 3 (3rd April 2017) - Anderson, Wineaster; Mdemu Komba, Immakulata
ABSTRACT: This study attempts to link poverty alleviation with specific sectors and gender in the context of a developing country, focusing on, female hairstylists in Tanzania. Using the absolute definition of poverty based on income/consumption in relation to specific nationally and internationally defined living standards, the study examined the income and consumption patterns of 230 women engaged in the hairstyling business in Dar es Salaam, Tanzania. Findings suggest that female entrepreneurs in the business earn more relative to conventionally defined indicators. Their earnings have improved their consumption, investments and savings, and enabled them to fulfil their dependents' basic needs.